The Effect of Carrageenan Concentration on the Physical, Chemical Characteristics and Preference Levels of Watermelon Albedo and Red Dragon Fruit Sheet Jam - Agus Setiyoko; Soraya Kusuma Putri (Indonesian Journal of Food Technology, 2023)
This study aimed of this study was to find out how carrageenan affected the physical, chemical, and consumer preference characteristics of an albedo sheet jam combination made from red dragon fruit and watermelon. Four amounts of carrageenan addition— 0%, 1%, 1.5%, and 2%; three repeatations; and a one-factor Completely Randomized Design (CRD)—were employed in this investigation. Analysis. The sheet jam's texture, color, water content, total dissolved solids, reducing sugars, antioxidant activity, Vitamin C concentration, and hedonic tests were all examined after that. The SPSS program is used in statistical data processing to perform one-way analysis (one-way ANOVA). Using the Duncan approach, more study was conducted to determine the variations between treatments. The hedonic test was used to identify the chosen sheet jam formulation, which also included the inclusion of 1% carrageenan concentration, and the following quality test findings were obtained: Lightness (L) 20.19, redness (a*) 7.11, yellowness (b*) -1.87, texture 652.15 N/mm2, water content 18.28% wb, total dissolved solids 21.29% 0 brix, reducing sugars 46.35%, antioxidant activity of RSA 19.32%, and vitamin C 9.14 mg/100 g.